Managing the “Maju Bersama” Village-Owned Enterprise in Suka Maju Village, Kampar Regency - Rini Rahayu; Rony Jaya (CV Insan Kreasi Media, 2026)
Effective management of Village-Owned Enterprises (BUM Des) can boost the village economy and independence, but in reality, many BUM Des are still not optimally managed. The purpose of this article is to analyze the management of BUM Des Maju Bersama in Suka Maju Village, Tapung Hilir District, Kampar Regency and identify obstacles in its management. The study used a descriptive qualitative method with data collection techniques in the form of interviews and documentation. Informants were selected through purposive sampling involving fifteen informants, consisting of the Village Head ex-officio Commissioner, Supervisor, Director, Secretary, Treasurer, and ten community members. Interactive data analysis was carried out through stages of condensation, presentation, drawing conclusions, and verification that ensured the validity of the data through triangulation of sources and techniques. The results of the study indicate that BUM Des management is carried out based on legal provisions and has involved the community in a participatory manner, but its management is still not running optimally. Identification of management obstacles includes immature business planning, weak commitment, managerial capacity and coordination between administrators, and ineffective evaluation.